Perancanaan Strategis SI/TI Menggunakan Four Stage Model Pada Dinas Pendidikan Kabupaten Kubu Raya Kalimantan Barat - Rabiatul Adwiya (Universitas Bina Sarana Informatika, 2015)
Strategic planning is one of the effort in order to the factor organizations can do strategic planning. To reach the building of SI / TI to official education needed strategic planning, that plan a system for the future. Realization of building S/TI influeneed by important factor, generally not enough yet such as: infrastructure of communication and information, penetrations of computer and internet, human resource, applications, organizations and procedure system, funds and etc. For that problems, so strategic of building SI/TI with case from official education Kabupaten Kubu Raya meaning for a basic guide SI/TI of field application system only. Approaching that use is Four Stage Model Methodology, that modificated necessary to adapt with typical organization, Sector of official education. The expectation is to reach a uniformmity of planning development application in SI/TI area and to creat human resource that competent in SI/TI area. Trough this research, writer expected the end of result from this research can give a basic thinking for development application system SI/TI that comprehensive, efficient, effective according to capability from Official Education Kabupaten Kubu Raya that will be standard of implementation, so that finally can be realized a system of SI/TI. Result of this research in individual or organization in every instance goverment.Keyword: Official Education of Kabupaten Kubu Raya, Strategic Planning SI/TI, Four Stage Model Methodology.